Five new species of Zercon C. L. Koch, 1836 (Acari: Zerconidae) from northwestern Turkey - Karaca, Mehmet; Urhan Raşi̇t (Zootaxa, 2016)
Mites belonging to the genus Zercon collected from the Thrace region in Turkey are investigated. Five new species, Z. filiformis sp. nov., Z. geliboluensis sp. nov., Z. sklarsimilis sp. nov., Z. tekirdagensis sp. nov. and Z. thracicus sp. nov., are described and illustrated. Zercon similifoveolatus Ivan & Călugăr is newly recorded for the Turkish fauna. Female specimens of Z. sklari Balan are reported and descibed for the first time in Turkey. Some known zerconid mites are recorded from new localities. A key to species of the genus Zercon known from Turkey is included.